Absorption, distribution and elimination behaviours of cadmium treated by in vitro DIN from WLP residue using SAAM II modeling - Yasmin Mohd Idris Perama; Nur Shahidah Abdul Rashid; Syazwani Mohd Fadzil; Khoo, Kok Siong (Penerbit Universiti Kebangsaan Malaysia, 2018)
Mathematically, the human alimentary tract organs were simplified in the model structure as separate compartments with pathways of transfer that are kinetically homogenous and equally distributed. The development of gastro-compartment model follows the first order kinetics of differential equations to describe cadmium absorption, distribution and elimination in the human digestive system. With the aid of in vitro DIN assay, an artificial gastric and gastrointestinal fluid were prepared using water leach purification (WLP) residue as a sample that contained toxic metals cadmium. The Simulation, Analysis and Modelling II (SAAM II) V2.1 software is employed to design models easily, simulate experiments quickly and analyze data accurately. Based on the experimental inputs and fractional transfer rates parameter incorporated to the gastro-compartment model, the concentration of cadmium against time profile curves were plotted as the model output. The curve presented concentration of cadmium in both gastric and gastrointestinal fluid where initially absorption phase (first hour) occurred followed by the distribution phase (second to third hours) and elimination process (third to fifth hours). The concentration of cadmium obtained from the simulated model structures was in good agreement with the fitted model predicted measurements as statistical t-test conducted showed the values were not significantly different. Therefore, modeling approach with SAAM II software gave realistic and better estimation of cadmium dissolution into the human gastrointestinal tract.